The Cambridge companion to Gulliver's travels - Cook, Daniel 1981-; Seager, Nicholas ca. 20./21. Jh (Cambridge University Press, 2024)
Jonathan Swift's satirical masterpiece, Gulliver's Travels, has shocked and delighted readers worldwide since its publication in 1726. At turns a humorous and harrowing indictment of human behaviour, it has been endlessly reinterpreted by critics and adapted across media by other artists. The Cambridge Companion to Gulliver's Travels comprises 17 original chapters by leading scholars, written in a theoretically-informed but accessible style. As well as providing detailed close readings of each part of the narrative, this Companion relates Gulliver's Travels to the political, religious, scientific, colonial, and intellectual debates in which Swift was engaged, and it assesses the form of the book as a novel, travel book, philosophical treatise, and satire. Finally, it explores the Travels' rich and varied afterlives: the controversies it has fuelled, the films and artworks it has inspired, and the enduring need authors have felt to 'write back' to Swift's original, disturbing, and challenging story
Keywords: Swift, Jonathan -- 1667-1745 -- Gulliver's travels; Aufsatzsammlung